HEMODİYALİZ HASTALARININ YAŞAM KALİTESİNİN ULUSLARARASI MUKAYESELİ ANALİZİ - (:unkn) unknown (My University, 2016)
Bu araştırmanın amacı, Türkiye'de tedavi gören hemodiyaliz hastalarının yaşam kalitesini belirleyen unsurların uluslararası mukayesesini yapmaktır. Araştırma örneğine giren 236 hemodiyaliz hastasının içinde bulundukları durumla ilgili fiziksel ve duygusal sorunlarına ilişkin algıları KDQOL-SF Versiyon 1.3 (böbrek hastalığı yaşam kalitesi) ölçüm aracı kullanılarak ölçülmüştür. Araştırma sonuçları Türk hemodiyaliz hastalarının diğer ülkelerdeki hemodiyaliz hastalarına göre daha yüksek yaşam kalitesi algısına sahip olduklarını göstermiştir. Benzer şekilde diyaliz personelinin cesaretlendirmesi, hasta tatmini, zihinsel işlev ölçekleri haricinde diğer tüm alt-ölçeklerde Türk hemodiyaliz hastalarının daha yüksek yaşam kalitesi algısına sahip oldukları belirlenmiştir

Aim of the study is to make international comparisons on the determinants of quality of life of the dialysis patients who received treatment in Turkey. Determinants (sub-scales) of quality of life of the dialysis patients are measured by KDQOL-SFTM Version 1.3 (Kidney Disease Quality of Life) instrument. A sample of 236 dialysis patients responded to those questions in the instrument of KDQOL-SF Version 1.3 based on their perceptions about their physical and emotional problems. The research results showed that Turkish hemodialysis patients perceived their quality of life higher than other countries and similar results obtained for the determinants (sub-scales) of the instrument other than the sub- scales of staff encouragement, patient satisfaction and mental health
INTERNATIONAL COMPARATIVE ANALYSIS OF THE QUALITY OF LIFE OF HEMODIALYSIS PATIENTS
Keywords: Biyoloji